Multimodality Analysis of Visual and Linguistic Signs in the Arabic Version of Indomie Export Packaging in the Construction of Global Meaning - Muhamad Maulana Yusup; Novy Maryani (Gunung Djati Conference Series, 2026)
This study aims to analyze the construction of global meaning through the interaction of visual and linguistic signs on the packaging of Indomie export products in the Arabic version compared to the Indonesian domestic version. Using a library research method with a qualitative approach, this study applies Social Semiotics theory and the Grammar of Visual Design (GVD) proposed by Kress and van Leeuwen to examine the integrated modes of communication. The findings reveal significant semiotic adaptation strategies, in which verbal elements employ Arabic script to enhance information accessibility, while visual elements, particularly food illustrations, are modified to accommodate local culinary preferences in the Middle Eastern market. Spatially, the export packaging adopts a right-to-left reading pattern to ensure effective information value for target consumers. This study concludes that Indomie’s success in the global market relies on its ability to negotiate identity through multimodal curation that balances universal brand identity with local socio-cultural relevance. These findings contribute theoretically to strengthening multimodal literacy in international product packaging design.